Asymptotic expansion of solutions of quasilinear parabolic problems in perforated domains - Skrypnik, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The asymptotic expansion of solutions to quasilinear parabolic problems with the Dirichlet boundary condilions is constructed in the regions with a fine-grain boundary. It is shown that the sequence of the remainders of the expansion strongly converges to zero in the space W^1,1/2_2.